ANALYSIS OF ARITHMETIC DIFFICULTIES AMONG ELEMENTARY SCHOOL STUDENTS - Enda Lovita Pandiangan; Dian Anggeraini; Nurul Putri Aulia; Maulida Khairunnisa; Vira Marsella (El Midad, 2024)
This study aims to identify the learning difficulties of grade VI students in arithmetic at MIS YPII Tanjung Pura and analyze the factors influencing these difficulties. A quantitative method with a descriptive approach was employed for data collection through questionnaires and analysis of student scores. The questionnaire consisted of 20 statements with "Yes" or "No," focusing on aspects such as motivation, conceptual understanding, and support from the learning environment. Additionally, student score data were analyzed to identify patterns of learning difficulties. The results showed that 54.7% of students had difficulty understanding basic arithmetic operations, particularly in multiplication and division. Furthermore, 66.7% of students felt insecure when faced with math problems, and 77.8% expressed needing additional guidance outside of school. Internal factors, such as low motivation and anxiety about math, and external factors, including monotonous teaching methods and minimal parental support, negatively impacted learning outcomes. Data indicated that 50% of students scored below the passing standard. This study recommends using interactive learning strategies, utilizing visual media, and enhancing collaboration between teachers and parents to better support students in their learning processes